AFFINITY BIOSENSOR BASED ON SCREEN-PRINTED ELECTRODE MODIFIED WITH DNA FOR GENOTOXIC COMPOUNDS DETECTION - Bambang Kuswandi (Indonesian Journal of Chemistry, 2008)
An electrochemical method for the detection of the genotoxic compounds using a DNA-modified electrode was developed. This electrode was successfully used for the electrochemical detection of genotoxic compounds in water samples. The electrochemical results clearly demonstrated that, the development is related to the molecular interaction between the surface-linked DNA obtained from calf thymus and the target compounds, such as pollutants, in order to develop a simple device for rapid screening of genotoxic compounds in environmental samples. The detection of such compounds was measured by their effect on the oxidation signal of the guanine peak of the DNA immobilised on the surface of carbon based Screen-Printed Electrode (SPE) in disposable mode, and monitored by square-wave voltametric analysis. The DNA biosensor is able to detect known intercalating and groove-binding genotoxic compounds such as Dioxin, Bisphenol A, PCBs, and Phtalates. Application to real water samples is discussed and reported.